Hubungan Perilaku Merokok Ibu dengan Kejadian Ispa Pada Balita di Indonesia: Analisa Data SDKI 2017 - Mursalin, Mursalin; Maidar, Maidar; Nurjannah, Nurjannah; Abdullah, Asnawi; Saputra, Irwan (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT The percentage of children experiencing ARI in Indonesia has increased from 5% in 2012 to 24% in 2017. One of the most risk factors for causing ARI in children is exposure to cigarette smoke. Analyzing the relationship between maternal smoking behavior and the incidence of ISPA in toddlers in Indonesia. This research is descriptive analytic by using a cross-sectional design to determine the relationship between smoking behavior of parents with the incidence of ARI in children under five in Indonesia. This study used secondary data from the 2017 IDHS. The number of samples in the study was 17,156 children under five. Multivariate analysis using multiple logistic regression test. Toddlers who experienced ARI were 7.04%. The smoking behavior factor which is significant with the incidence of ARI in children under five in Indonesia is smoking mothers (p-value = 0.032; OR = 1.43). The most dominant family factor related to the incidence of ARI among children under five in Indonesia is mothers with low education (p-value = 0.001; AOR = 1.36). The most dominant factor associated with the incidence of ARI among children under five in Indonesia is low birth weight (p-value = 0.003; AOR = 1.38). The most dominant factor associated with the incidence of ARI among children under five in Indonesia after adjusting for other variables was maternal smoking (p-value=0.035; OR=1.43). Mothers who smoke are 43% at risk of causing toddlers to experience ARI compared to mothers who do not smoke. Conclusion: Mother's smoking behavior is related to ARI in toddlers, so it is recommended that mothers who have toddlers do not smoke in the house and when they are with their children. Keywords: ARI, Maternal Smoking Behavior, Toddler Factor, Family Factor  ABSTRAK Persentase anak yang mengalami ISPA di Indonesia mengalami peningkatan dari tahun 2012 sebanyak 5% meningkat menjadi 24% pada tahun 2017. Salah satu faktor yang paling berisiko menyebabkan terjadinya ISPA pada anak yaitu paparan asap rokok. Tujuan untuk menganalisis hubungan perilaku nerokok ibu dengan kejadian ISPA pada balita di Indonesia. Penelitian ini bersifat deskriptif analitik dengan menggunakan desain cross-sectional untuk mengetahui hubungan perilaku merokok ibu dengan kejadian ISPA pada balita di Indonesia. Penelitian ini menggunakan data sekunder SDKI 2017. Jumlah sampel dalam penelitian yaitu 17,156 balita. Analisa multivariat menggunakan uji regresi logistik berganda. Balita yang mengalami ISPA sebanyak 7,04%. Faktor perilaku merokok yang signifikan dengan kejadian ISPA pada balita di Indonesia adalah ibu merokok (p-value=0,032; OR=1,43). Faktor keluarga yang paling dominan berhubungan dengan kejadian ISPA pada balita di Indonesia adalah ibu yang berpendidikan rendah (p-value=0,001; AOR=1,36). Faktor balita yang paling dominan berhubungan dengan kejadian ISPA pada balita di Indonesia adalah berat badan lahir rendah (p-value=0,003; AOR=1,38). Faktor yang paling dominan berhubungan dengan kejadian ISPA pada balita di Indonesia setelah disesuaikan dengan variabel lain adalah ibu merokok (p-value=0,035; OR=1,43). Ibu yang merokok 43% berisiko menyebabkan balita mengalami ISPA dibandingkan dengan ibu yang tidak merokok. Perilaku merokok ibu berhubungan dengan ISPA pada balita, sehingga diharapkan kepada ibu yang memiliki balita untuk tidak merokok di dalam rumah dan saat bersama dengan anak. Kata Kunci: ISPA, Perilaku Merokok Ibu, Faktor Balita, Faktor Keluarga